2003
DOI: 10.1177/14713012030023006
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Spirituality, and Ethnicity

Abstract: Caregivers of persons with Alzheimer's disease (AD) provide an inordinate and escalating level of care. It has been postulated that: (1) religious beliefs and/or spirituality may assist individuals in their caregiving efforts; and (2) coping strategies may vary depending on ethnicity. The intent of this pilot study was to examine these theories by interviewing five African-American and five white caregivers of persons with AD using demographic and open-ended questions regarding spirituality, religious practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Thus, the emphasis of CIT-S on family collectivism and spirituality in confronting the illness may make the treatment approach especially relevant and culturally sanctioned for minorities. On the other hand, research suggests that perceived family unity (Varela, Sanchez-Sosa, Biggs, & Luis, 2009) and spirituality (Nightingale, 2003) may benefit Whites coping with adversity as well. Because Whites may be less likely than their minority counterparts to already be engaging in spiritual practices and to turn to family for support, they may have even more to gain from a treatment intervention that incorporates these approaches.…”
Section: Patient Ethnicity and Patient-therapist Ethnic Match And Satmentioning
confidence: 99%
“…Thus, the emphasis of CIT-S on family collectivism and spirituality in confronting the illness may make the treatment approach especially relevant and culturally sanctioned for minorities. On the other hand, research suggests that perceived family unity (Varela, Sanchez-Sosa, Biggs, & Luis, 2009) and spirituality (Nightingale, 2003) may benefit Whites coping with adversity as well. Because Whites may be less likely than their minority counterparts to already be engaging in spiritual practices and to turn to family for support, they may have even more to gain from a treatment intervention that incorporates these approaches.…”
Section: Patient Ethnicity and Patient-therapist Ethnic Match And Satmentioning
confidence: 99%
“…Previous research has indicated that African-Americans benefit physically, psychologically, and socially when they are involved with religious organizations [12]. Religion and religious institutions have assisted African-Americans both materially and psychologically [13] [14] [15] [16]. And research has consistently highlighted the importance of the African-American church for individuals, couples, and families.…”
Section: Methodsmentioning
confidence: 99%
“…(Chang et al 1998;Murray-Swank et al 2006;Pierce et al 2008). Nightingale (2003) reported that religion and spirituality help caregivers to deal with the hard challenges of patient's care. However, Hebert et al (2006) reviewed the literature on the relationship between religion ⁄ spirituality and well-being of caregivers and notified that most of the researches on this issue report a mixed and unclear relationship (e.g.…”
Section: Religious Tendenciesmentioning
confidence: 99%
“…2008). Nightingale (2003) reported that religion and spirituality help caregivers to deal with the hard challenges of patient’s care. However, Hebert et al.…”
Section: Introductionmentioning
confidence: 99%